2016
DOI: 10.1016/j.rehab.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation (exercise and strength training) and osteoarthritis: A critical narrative review

Abstract: Rehabilitation is widely recommended in national and international guidelines for managing osteoarthritis (OA) in primary care settings. According to the 2014 OA Research Society International (OARSI) recommendations, rehabilitation is even considered the core treatment of OA and is recommended for all patients. Rehabilitation for OA widely includes land- and water-based exercise, strength training, weight management, self-management and education, biomechanical interventions, and physically active lifestyle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 35 publications
1
53
0
5
Order By: Relevance
“…Rehabilitation for hip OA encompasses several different aspects, including patient education, weight management, land- and water-based exercise, and strength training [144]. While consistent evidence supports the efficacy of these strategies in the management of knee OA [145], the evidence in hip OA is far more variable [144].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation for hip OA encompasses several different aspects, including patient education, weight management, land- and water-based exercise, and strength training [144]. While consistent evidence supports the efficacy of these strategies in the management of knee OA [145], the evidence in hip OA is far more variable [144].…”
Section: Managementmentioning
confidence: 99%
“…While consistent evidence supports the efficacy of these strategies in the management of knee OA [145], the evidence in hip OA is far more variable [144]. Weight loss is recommended for people with hip OA who are overweight/obese; however unlike knee OA, there is a paucity of clinical trial evidence for weight loss in hip OA [146].…”
Section: Managementmentioning
confidence: 99%
“…2 Improved strength can lead to decreased joint loading and increased joint stability. 12 A 2011 systematic review on the effect of strength training for knee OA showed moderate effect size for both decreasing pain and improving function. 2 Few studies evaluate the effectiveness of physical therapy for delaying progression of OA to the endpoint of joint replacement.…”
Section: Physical Therapy/strength Trainingmentioning
confidence: 99%
“…Among the conservative treatments available for OA, exercises have been shown to be cost-effective and useful in improving quality of life [6]. Exercise aims to reduce the magnitude of change observed in strength, joint range of motion, proprioception, and alignment, which are often impaired due to the natural course of the disease and disuse [7]. Such impairments lead to reductions in function and quality of life [8].…”
Section: Introductionmentioning
confidence: 99%